Zika virus is not thermostable: very effective virus inactivation during heat treatment (pasteurization) of human serum albumin. Issue 3 (17th December 2016) - Farcet, Maria R.; Kreil, Thomas R.
Abstract : BACKGROUND: The ongoing Zika virus (ZIKV) outbreak in the Americas has also raised concerns around the potential for ZIKV transmission via blood products. Plasma‐derived products are considered safe, because effective viral‐inactivation and removal methods are implemented in their manufacturing processes. However, a recent study has indicated that ZIKV is "thermally stable" compared with the closely related Dengue virus, thus raising the question of whether heat treatments, as embedded in the manufacturing of plasma‐derived products, are as effective against ZIKV as was previously shown for other Flaviviruses. Therefore, the sensitivity of ZIKV to heat inactivation was investigated using the pasteurization of human serum albumin (HSA) as an example. STUDY DESIGN AND METHODS: Heat treatment (58.0 ± 1.0°C for 590 ± 10 minutes) of HSA was investigated for the capacity to reduce ZIKV in two different protein concentrations (5% and 25% HSA). The results were compared with data obtained in identical set‐ups for the closely related West Nile virus, tick‐borne encephalitis virus, and bovine viral diarrhea virus. RESULTS: Heat treatment of HSA inactivated ZIKV to below the limit of detection already during the heating phase to 57.0°C, that is, even before the 10‐hour incubation at 58.0 ± 1.0°C commenced. For West Nile virus, bovine viral diarrhea virus, and tick‐borne encephalitis virus, incubations up to 180 minutes were required to achieve inactivation to below the limit of detection. CONCLUSION: ZIKV was more sensitive to heat treatment than other members of the Flaviviridae and thus does not pose a concern for plasma products that include a heat treatment in their manufacturing process.